Workers, Firms and Life-Cycle Wage Dynamics - Paul Bingley; Lorenzo Cappellari (Institute of Labor Economics (IZA), 2018)
Studies of individual wage dynamics typically ignore firm heterogeneity, whereas decompositions of earnings into worker and firm effects abstract from life-cycle considerations. We study firm effects in individual wage dynamics using administrative data on the population of Italian employers and employees. We propose a novel identification strategy for firm-related wage components exploiting the informative content of the wage covariance structure of coworkers. Wage inequality increases three-fold over the working life; firm effects are predominant while young, but sorting of workers into firms becomes increasingly important, explaining the largest share of lifetime inequality. Static models that do not allow for life-cycle dynamics underestimate the importance of sorting and overstate match and firm effects.
Keywords: J24; J31; 330; wage inequality; wage dynamics; co-workers' covariance